Chronic arsenic exposure promotes cell migration via KEAP1-mediated F-actin cytoskeletal rearrangement - Xin Fang; Junyi Wang; Xianhang Yin; Maojia Fu; Yuxin Hu; Huihui Wang; Jingbo Pi; Yuanyuan Xu (Toxicology and Applied Pharmacology, 2026)

Multi-scale drivers of spontaneous plant diversity in urban residential green spaces across dispersal modes: Implications for ecological planning - Chengyu Ran; Yankai Huang; Yuxiang Liu; Junyi Pan; Ziang Su; Yujun Chen; Weicong Fu (Journal of Environmental Management, 2026)

Polychlorinated biphenyl pollution as an unintentional major contaminant in the Pearl River Delta, China - Hongbing Wang; Chenglong Wei; Guowei Fu; Daheng Zhang; Miao Fu; Junyi Jiang; Yue Long; Yanwei Song (Environmental Research, 2025)

Highly stretchable, self-adhesive, conductive, and tough hydrogel reinforced with cellulose nanofibers for wearable biosensor and ultrasonic nanogenerator - Yijun Fu; Junyi Zou; Yijie Wang; Zhengyu Yao; Pengfei Lv; Dingsheng Wu; Qufu Wei; Wei Zhang; Yu Jiang; Dawei Li (Chemical Engineering Journal, 2025)

The path of corporate low-carbon behavioral change: The impact of digital transformation on corporate green sports brand loyalty - Junyi Li; Zhengfan Xie; Yu Fu (Journal of Environmental Management, 2025)

Study on the characteristics of bird communities in urban river corridor parks and green spaces - Yinghong Ding; Dulai Zheng; Yuxin Lin; Junyi Li; Weicong Fu; Ziru Chen; Jin Yang; Xiaoling Xu; Zhipeng Zhu (Environment, Development and Sustainability, 2025)

Large-scale ecological infrastructures enhance the productivity of agro-socio-ecological systems by reducing soil erosion in the Loess Plateau - Fen Gou; Wei Liang; Yan Liu; Bojie Fu; Zhenguo Wang; Weibin Zhang; Zhigang Chen; Jianwu Yan; Junyi Li; Yihe Lv (Journal of Environmental Management, 2025)

Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metal(loid)s in surface sediments of the nearshore area of Qionghai - Junyi Jiang; Miao Fu; Jianying Yang; Yanwei Song; Guowei Fu; Hongbing Wang; Cong Lin; Yang Wang (Frontiers in Marine Science, 2024)
To understand the pollution characteristics and potential sources of heavy metal(loid)s in the nearshore sediments of Qionghai, 93 surface sediment samples were collected from the region. The concentrations of 20 elements, including Fe, Mg, Ca, Ti, Mn, Ba, Cr, Sr, Ni, Cu, Zr, As, Hg, Se, Be, Co, Mo, Cd, Ga, and Pb, were measured. The extent of contamination and ecological risk posed by these heavy metals/metalloids were evaluated using the geo-accumulation index, potential ecological risk index, and Nemerow comprehensive risk index. Additionally, correlation analysis, principal component analysis (PCA), and positive matrix factorization (PMF) were employed to identify the potential sources of these elements in the sediments. The findings reveal the following: (1) The mean concentrations of Fe, Ca, Mg, Ti, Cu, Sr, Zr, Mo, Cd, Pb, Hg, As, and Se exceed the background values for shallow sea sediments in China. Notably, Ca, Ti, Sr, Zr, Mo, Hg, and As exhibit coefficients of variation greater than 51%, indicating significant spatial variability primarily driven by anthropogenic activities. (2) The ecological risk assessment identifies Sr, Hg, and As as the principal pollutants and key potential ecological risk factors in the study area, necessitating prioritization in subsequent monitoring efforts. (3) Correlation and source analysis suggest that As and Mn primarily originate from agricultural activities, Sr, Ca, and Mg from aquaculture, Zr, Ti, Mo, Se, Pb, Be, Co, Cu, Ga, Ni, Fe, and Cd from natural sources, and Hg, Ba, and Cr from transportation sources. Additionally, this study identified Sr, Hg, and As as the primary pollutants in the Qionghai nearshore area, with sources predominantly linked to agriculture, aquaculture, and traffic. Regular monitoring will help track the effectiveness of implemented control measures and provide data for ongoing risk assessments, ensuring the protection and sustainability of the marine environment.

Uncovering the structure and evolution of global virtual water and agricultural land network - Zhenguo Wang; Tengyun Li; Wei Liang; Bojie Fu; Junyi Li; Jianwu Yan (Sustainable Production and Consumption, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Assessment of the community status of seagrass bed and its relationship with environmental characteristics in Wenchang, Hainan Island, China - Miao Fu; Junyi Jiang; Dacheng Wang; Guowei Fu; Yanwei Song; Hongbing Wang; Daheng Zhang (Frontiers in Marine Science, 2024)
As one of the typical coastal ecosystems, seagrass bed has important ecological service functions. In order to enrich the basic data of multispecies tropical seagrass beds, the main controlling factors affecting the community status of seagrass were identified. In this study, the species, distribution and community characteristics of seagrass in Wenchang were investigated at five stations in 2023, and Spearman correlation analysis and Redundancy analysis were used to investigate the relationship between seagrass and environmental characteristics. The results showed that there were 7 species of seagrass belonging to 5 genera in 2 families along Wenchang coast, including Enhalus acoroides , Thalassia hemprichii , Cymodocea rotundata , Cymodocea serrulata , Halophila ovalis , Halophila minor and Halodule uninervis . The distribution of seagrass beds in Wenchang showed an obvious trend of degradation. Except for the relatively stable of seagrass beds in the central part of Wenchang, the seagrass beds on both the north and south sides decreased significantly, and the coverage of seagrass beds decreased from 24.31% in 2016 to 21.0% in 2020, and further decreased to 20.67% in 2023. The data showed that the coverage and aboveground biomass of seagrass were significantly positively correlated with temperature, and the density of seagrass was significantly positively correlated with DO, but significantly negatively correlated with COD. In addition, increased nutrient salts in the water column could negatively affect seagrass bed. In order to promote the sustainable development of seagrass ecosystem and enhance the stability of seagrass habitat, it is suggested to rationally plan the aquaculture scale of the surrounding area; flexibly manage the rake snail, rake clam and other fishing activities, appropriately reduce the frequency of mining; and scientifically plan marine engineering to reduce the damage to seagrass bed.

Electrospun PAN/BaTiO3/MXene nanofibrous membrane with significantly improved piezoelectric property for self-powered wearable sensor - Yijun Fu; Jiahao Liu; Junyi Zou; Sijun Xu; Yanhong Wei; Wei Zhang; Dawei Li (Chemical Engineering Journal, 2024)

A study on the impact of the carbon emissions trading policy on the mining industry based on Porter hypothesis - Yaxin Zhang; Shibo Zeng; Qiaosheng Wu; Junyi Fu; Tongping Li (Resources Policy, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Effects of different particle-sized insoluble dietary fibre from citrus peel on adsorption and activity inhibition of pancreatic lipase - Ben Yu; Qingmiao Tang; Caixia Fu; Joe Regenstein; Junyi Huang; Lufeng Wang (Food Chemistry, 2023)

Genetic variants in Hippo signalling pathway-related genes affect the risk of colorectal cancer - Hengyang Shen; Yixuan Meng; Tao Hu; Shuwei Li; Mulong Du; Junyi Xin; Dongying Gu; Meilin Wang; Zan Fu (Archives of Toxicology, 2021)

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Grassland gross carbon dioxide uptake based on an improved model tree ensemble approach considering human interventions: global estimation and covariation with climate - Wei Liang; Yihe Lü; Weibin Zhang; Shuai Li; Zhao Jin; Philippe Ciais; Bojie Fu; Shuai Wang; Jianwu Yan; Junyi Li; Huimin Su (Global Change Biology, 2017)
Grassland ecosystems act as a crucial role in the global carbon cycle and provide vital ecosystem services for many species. However, these low‐productivity and water‐limited ecosystems are sensitive and vulnerable to climate perturbations and human intervention, the latter of which is often not considered due to lack of spatial information regarding the grassland management. Here by the application of a model tree ensemble ( MTE ‐ GRASS ) trained on local eddy covariance data and using as predictors gridded climate and management intensity field (grazing and cutting), we first provide an estimate of global grassland gross primary production ( GPP ). GPP from our study compares well (modeling efficiency NSE = 0.85 spatial; NSE between 0.69 and 0.94 interannual) with that from flux measurement. Global grassland GPP was on average 11 ± 0.31 Pg C yr −1 and exhibited significantly increasing trend at both annual and seasonal scales, with an annual increase of 0.023 Pg C (0.2%) from 1982 to 2011. Meanwhile, we found that at both annual and seasonal scale, the trend (except for northern summer) and interannual variability of the GPP are primarily driven by arid/semiarid ecosystems, the latter of which is due to the larger variation in precipitation. Grasslands in arid/semiarid regions have a stronger (33 g C m −2 yr −1 /100 mm) and faster (0‐ to 1‐month time lag) response to precipitation than those in other regions. Although globally spatial gradients (71%) and interannual changes (51%) in GPP were mainly driven by precipitation, where most regions with arid/semiarid climate zone, temperature and radiation together shared half of GPP variability, which is mainly distributed in the high‐latitude or cold regions. Our findings and the results of other studies suggest the overwhelming importance of arid/semiarid regions as a control on grassland ecosystems carbon cycle. Similarly, under the projected future climate change, grassland ecosystems in these regions will be potentially greatly influenced.

The long persistence of pyrrolizidine alkaloid-derived DNA adducts in vivo: kinetic study following single and multiple exposures in male ICR mice - Lin Zhu; Junyi Xue; Qingsu Xia; Peter P. Fu; Ge Lin (Archives of Toxicology, 2017)

Mapping of SMV resistance gene Rsc-7 by SSR markers in soybean - Sanxiong Fu; Yong Zhan; Haijian Zhi; Junyi Gai; Deyue Yu (Genetica, 2006)

Characterizing the cytoplasmic diversity and phyletic relationship of Chinese landraces of soybean, Glycine max, based on RFLPs of chloroplast and mitochondrial DNA - Yoshiya Shimamoto; Jun Abe; Zhong Gao; Junyi Gai; Fu-Sheng Thseng (Genetic Resources and Crop Evolution, 2000)